Isolation and Identification of Salmonella Spp. Bacterial Pathogens from Frozen Chickens Meat in Diyala Province - Mohammed, Ayat Jasim; Khadim, Mahmood Ahmed; Hassoon, Shaymaa Jabbar (Diyala Journal for Veterinary Sciences, 2023)
Background: Chicken meat is widely used by humans all over the world. Frozen chicken (meats) are produced at meat processing plants as well as at home and has been identified as the main cause of food-borne Salmonellosis. Aims: The aim of this study was to examine the major food-borne pathogen Salmonella spp. from frozen chicken meat samples of local and imported chickens obtained from the different local markets in Diyala Province/Iraq. Eighty samples were taken from a local market to detect Salmonella spp. forty frozen samples of local chicken meat and 40 frozen samples of imported chicken meat were used in this study Results: Primary samples were cultured and placed in peptone water. Using traditional microbiological procedures, colonies were discovered. salmonella spp. was found at higher rates in meat samples from the local market. The identification rate of Salmonella spp. were 7.5% and 17.5% of imported frozen chicken meat and local frozen chicken meat, respectively. Conclusions: hygienic standards of local frozen chicken meat is critical as Salmonella spp was higher in local frozen chicken meat compared with imported meat .